2021
DOI: 10.1515/jpm-2020-0541
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s psychological state and influence factors: anxiety, and depression during COVID-19 outbreak

Abstract: Objectives The outbreak of COVID-19 affects both physical and mental health of pregnant women. This study focuses on their psychological status, and analyzes the main factors affecting their emotions of pregnant women so as to provide guidance for psychological counseling and social intervention during epidemics. Methods Multiple researchers distributed a questionnaire online via the Internet. Pregnant women volunteered, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In addition, we found respondents’ lives seriously impacted by the coronavirus were more likely to have psychological problems. Possible reasons are an inconvenience in obtaining antenatal examinations, lack of social and family support, and income losses because of a social isolation policy ( Li et al, 2020 ; Cao et al, 2021 ). Consistent with our findings, many studies have demonstrated that physical exercise could reduce anxiety and depression symptoms in pregnant women and therefore could be an effective strategy to enhance mental health ( Farrell et al, 2020 ; Colli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found respondents’ lives seriously impacted by the coronavirus were more likely to have psychological problems. Possible reasons are an inconvenience in obtaining antenatal examinations, lack of social and family support, and income losses because of a social isolation policy ( Li et al, 2020 ; Cao et al, 2021 ). Consistent with our findings, many studies have demonstrated that physical exercise could reduce anxiety and depression symptoms in pregnant women and therefore could be an effective strategy to enhance mental health ( Farrell et al, 2020 ; Colli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Edinburgh Postnatal Depression Scale (EPDS) was primarily applied for screening postpartum depression, it was also validated as being useful for pregnant women with good reliability and validity. 5 It is a 10-item scale that requires participants to appraise their depression-related symptoms from 0 (never) to 3 (always). The scores in each question were summed, and a final score ≥ 9 defined the state for depression.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research shows that the pandemic situations may affect people's emotional state and that misinformation or deficiencies of health systems in providing information and preparing the population to have appropriate attitudes may have a negative psychological impact ( Cao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immuno-psycho-emotional vulnerability of pregnancy, in the context of the Covid-19 pandemic may increase, facilitating both the physical viral attack on the mother-foetus dyads as well as the psychological one ( Cao et al, 2021 ; Zanardo et al, 2020 ). Health systems should find solutions to provide additional psycho-emotional support to pregnant women during pandemics or any other unusual situations related to unpredictable natural disasters ( Ahmad and Vismara, 2021 ; Zanardo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%